Weight bias internalization, emotion dysregulation, and non‐normative eating behaviors in prebariatric patients. Issue 2 (23rd November 2015) - Baldofski, Sabrina; Rudolph, Almut; Tigges, Wolfgang; Herbig, Beate; Jurowich, Christian; Kaiser, Stefan; Dietrich, Arne; Hilbert, Anja
ABSTRACT: Objective: Weight bias internalization (WBI) is associated with eating disorder psychopathology and non‐normative eating behaviors among individuals with overweight and obesity, but has rarely been investigated in prebariatric patients. Based on findings demonstrating a relationship between emotion dysregulation and eating behavior, this study sought to investigate the association between WBI and eating disorder psychopathology as well as non‐normative eating behaviors (i.e., food addiction, emotional eating, and eating in the absence of hunger), mediated by emotion dysregulation. Method: Within a consecutive multicenter study, 240 prebariatric patients were assessed using self‐report questionnaires. The mediating role of emotion dysregulation was examined using structural equation modeling. Results: The analyses yielded no mediational effect of emotion dysregulation on the association between WBI and eating disorder psychopathology. However, emotion dysregulation fully mediated the associations between WBI and emotional eating as well as eating in the absence of hunger. Further, emotion dysregulation partially mediated the relationship between WBI and food addiction symptoms. Discussion: Prebariatric patients with high levels of WBI are at risk for non‐normative eating behaviors, especially if they experience emotion regulation difficulties. These findings highlight the importance of interventions targeting WBI and improving emotion regulation skills for the normalization of eating behavior in prebariatric patients. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:182–187).